DETERMINANTS OF PARENTERAL SUPPORT FOR CHILDHOOD MEASLES VACCINATION: A SYSTEMATIC REVIEW - Nurur Rachman Machmudy; Rofiqa Dwi Febriyanti; Asroful Hulam Zamroni; Ika Nur Pratiwi (International Journal of Patient Safety and Quality, 2026)
Background: Measles is caused by the measles virus; it is a serious, highly contagious disease that commonly affects children. The disease is transmitted through droplets from the nose, mouth, or throat of an infected person, with an incubation period of approximately 7 to 23 days. Methods: The purpose of this study was to describe, analyze, and elaborate on evidence related to the determinants of parental support for measles vaccination. To ensure methodological rigor, this review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: This systematic review included 15 quantitative studies published between 2020 and 2026, all of which demonstrated acceptable methodological quality based on the Joanna Briggs Institute (JBI) criteria, with the majority classified as having a low risk of bias. The included studies comprised 13 cross-sectional designs and 2 randomized controlled trials (RCTs), conducted across diverse settings, predominantly in Indonesia, as well as in Japan, France, The Gambia, and multi-country contexts across low- and middle-income regions in Africa and Asia. The study populations primarily consisted of parents or caregivers of children aged 0–59 months, although several studies incorporated broader population-level data and health system perspectives. Overall, the findings suggest that parental support for measles vaccination is influenced by a range of interrelated determinants. Conclusions: A systematic review indicates that parental support for measles vaccination is influenced by factors such as knowledge, sociodemographic characteristics, interactions with healthcare providers, cultural norms, and trust in information sources. Practical implications highlight the importance of personalized communication, training for healthcare workers, and the use of digital technology to address misinformation. Research gaps include the need for more in-depth studies on the role of extended families and the effectiveness of long-term digital interventions.